2020
DOI: 10.1007/s10072-020-04301-z
|View full text |Cite
|
Sign up to set email alerts
|

Listening to the neurological teams for multiple sclerosis: the SMART project

Abstract: Objective Aim of the research was to define the quality of life of Italian neurologists and nurses' professional caring for multiple sclerosis, to understand their living the clinical practice and identify possible signals of compassion fatigue. Material and methods One hundred five neurologists and nurses from 30 Italian multiple sclerosis centres were involved in an online quali-quantitative survey on the organization of care, combined with the Satisfaction and Compassion Fatigue Test and a collection of nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In particular, an Italian interview-based study of 105 HCPs and nurses showed that compassion fatigue and burnout were common due to intensive working practices, under-resourcing of medical personnel, and anxiety caused by employment conditions. 32 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, an Italian interview-based study of 105 HCPs and nurses showed that compassion fatigue and burnout were common due to intensive working practices, under-resourcing of medical personnel, and anxiety caused by employment conditions. 32 …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, determining elements of optimal communication between HCPs and PwMS about disease progression is challenging and no consensus exists. 19 , 29 , 32 , 36 The studies reviewed in this paper suggest that communication on disease progression with PwMS need to be delivered with sensitivity, at an appropriate time, and personalized to each patient’s disease, treatments, experiences, and understanding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term dedication can engender a sense of frustration and helplessness as patients’ illness progresses. Particularly, the constant exposure to patients’ suffering and distress, limited treatment effectiveness, no available cure, and working conditions often characterized by excessive workload, poor work autonomy, and inadequate staff can undermine health professionals’ daily work enjoyment and ultimately their job satisfaction [ 2 ].…”
Section: Introductionmentioning
confidence: 99%